Identification of key genes for mandibular prognathism in Duolang sheep via genome-wide association analysis - Fang, Chao; Liu, Ling-Ling; Liu, Wu-Jun; Farnir, Frederic (Frontiers in Veterinary Science, 2026)
Mandibular prognathism is a craniofacial trait that negatively affects feed intake in sheep and thus influences body weight and production performance. A genome-wide association study (GWAS) was conducted to identify genetic variants associated with mandibular prognathism (MP) in Duolang sheep. Phenotypes were classified into a binary trait: normal and MP. The analysis was based on whole-genome resequencing data from 221 individuals. We identified 48 potentially associated SNPs and 77 candidate genes related to mandibular prognathism. Based on gene functional analysis, we found five genes (PAX7, PLXNA4, CHD2, DZIP1, FBXW7) that may be involved in mandibular prognathism.Notably, seven SNPs on chromosome 4 were located within the PLXNA4 gene, and seven SNPs on chromosome 17 were located upstream of the FBXW7 gene. These findings provide novel insights into the genetic architecture of mandibular prognathism in sheep and offer potential molecular targets for future breeding and selection programs.